New observations on Urartian quarrying in Lake Van Basin - Kuvanç, Rıfat (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
Urartian architectural remains in eastern Turkey, Armenia, and north-western Iran bear witness to intensive quarrying during this period. Building materials at royal centres reveal that Urartians used local resources from the immediate vicinity of settlements, but they also carried out intensive quarrying at distant locations. Extraction, transportation, and processing of stone are labour-intensive activities which require a significant workforce. For these challenging undertakings, Urartians employed an effective administration of labour and advanced metal technology. The Urartian Kingdom marks an interesting starting point for quarrying in ancient Anatolia and the Near East in the 1st millennium BC. Sardurburç Building inscriptions at the north-western tip of Van Kalesi bear the first textual evidence for the name of a quarry, the city of Alniunu. Additionally, traces of quarrying near major settlements like Van Kalesi, Zivistan, Lower Anzaf, Upper Anzaf, Aznavurtepe, Ayanis, Çavuştepe, Körzüt, and Keçikıran in Lake Van Basin, and important water systems like the Minua Canal provide new information about stages of quarrying. Thin-section analysis of stone blocks sampled from Urartian centres allow us to determine the petrographic properties of building materials. Thin-section analyses reveal that sedimentary rocks (limestone, travertine, sandstone) and igneous rocks (gabbro, basalt, andesite) were used at Urartian centres.